Knowledge management in the STEM/STEAM teaching system - Teixeira, Flávia Dantas de Azevedo (2022)
STEAM education ("Science, Technology, Engineering, Art and Mathematics" in Portuguese, "Science, Technology, Engineering, Art and Mathematics") aims to cultivate model-literate citizens by empowering students with knowledge, skills and values ​​for the century. 21. Knowledge Management (KM) offers resources to enable these connections between disciplines and professors. This study has as general objective to analyze the possibility of the Ba environments (physical and virtual) to be mediated by the GC. The research is applied in nature with a qualitative approach through a hypothetical-deductive model with data collection via literature review. As a result, an analysis is presented on the possibility of physical and virtual environments being mediated by the KM, where the importance of establishing an environment conducive to the creation and sharing of knowledge was verified. In addition, efficient and systematic methods must be applied to manage knowledge within the teaching organization.